2010
DOI: 10.2110/jsr.2010.016
|View full text |Cite
|
Sign up to set email alerts
|

Large Distributive Fluvial Systems: Characteristics, Distribution, and Controls on Development

Abstract: An analysis of remotely sensed imagery reveals that fluvial planform geometries within aggrading continental areas are dominated by distributive fluvial systems (DFSs). We documented the gradient, length, apex location, planform, termination type, and tectonic and climatic setting of 415 examples of fluvial systems which in planform display a radial, distributive channel pattern and have an apex-toe distance . 30 km (large DFSs). The longest of these DFSs is 704 km in length, with the majority (72%) ranging be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
265
0
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 314 publications
(289 citation statements)
references
References 42 publications
11
265
0
13
Order By: Relevance
“…2H). Swamps and wetlands associated with DFS or 170 tributive fluvial systems were included in the DFS or tributive system, though we recognize that 171 wetlands may significantly affect facies locally (Hartley et al, 2010b Tandon and Sinha, 210 2007; Latrubesse, 2015). We also observed that the arrangement of fluvial geomorphic elements to be 211 consistent with the distributions described by DeCelles and Cavazza (1999) in most sedimentary basins 212 around the world (Fig.3).…”
Section: Introduction 70supporting
confidence: 59%
See 4 more Smart Citations
“…2H). Swamps and wetlands associated with DFS or 170 tributive fluvial systems were included in the DFS or tributive system, though we recognize that 171 wetlands may significantly affect facies locally (Hartley et al, 2010b Tandon and Sinha, 210 2007; Latrubesse, 2015). We also observed that the arrangement of fluvial geomorphic elements to be 211 consistent with the distributions described by DeCelles and Cavazza (1999) in most sedimentary basins 212 around the world (Fig.3).…”
Section: Introduction 70supporting
confidence: 59%
“…Rivers on these large DFS tend to enter the 345 sedimentary basin as broad, braided channel belts. Down-DFS, many of the channel belts diminish in 346 width, caused by infiltration, bifurcation, or evaporation, becoming single-thread channels with higher 347 sinuosity Hartley et al, 2010b;Weissmann et al, 2011). For example, the Bermejo River 348…”
Section: Andean Foreland Basin Chaco Plainmentioning
confidence: 99%
See 3 more Smart Citations